O crescimento de espécies arbóreas em plantios de restauração florestal e sua relação com atributos funcionais - Reis Júnior, José Carmelo de Freitas (Universidade Federal de São Carlos, 2017)
Forest restoration research focus mainly in tree growth and survival, missing research with functional aspects that explain evaluated growth parameters. Analyze functional attributes it is one of the ways to understand ecological strategies and function variations in organisms and, so useful to evaluate behaviors on different methods of restoration. Before that, we out lined hypothesis that growth, stated in basal area, of cover tree species was reduced in dense method or in under eucaliptus canopy method when compared o conventional method with 3 x 2 m and full sun. And the growth of these species in restoration methods was related to functional attributes. Six species were evaluated in three restoration methods. The species development, evaluated by basal area, varied according to the method. Generally, trees grew more in conventional method, with intermediate grew in under canopy method, and grew less in dense method. There was interaction between growth species in the different methods. Thus, the results indicate that some species would grow better than others in certain conditions, and future research should detail this aspects, searching change species for restoration projects. The basal area grew for species in methods was little explained by variations in functional strategy to explain the behavior of cover tree species.
The growth of cover tree species in forest restoration plantations and its relation with functional attributes
Keywords: Ecofisiologia; Ecologia funcional; Espécies de recobrimento; Plantios florestais; Restauração ecológica; Ecophysiology; Functional ecology; Cover species; Forest plantations; Ecological restoration; CIENCIAS AGRARIAS::AGRONOMIA